The Role of Creative Economics in Sei Nagalawan Mangrove Ecotourism Sector - Ayu Anggraini Tambunan; Tiomy Butsianto Adi; Tukijan Tukijan (Postgraduate, University of Mataram, 2024)
Sei Nagalawan Village in Serdang Bedagai Regency, Indonesia, utilizes the mangrove ecosystem for economic benefits through creative activities and fishing. However, long-term use raises ecological and social problems, requiring a balance between conservation and development. This post-positivism-based study explores the transformation of Sei Nagalawan into an ecotourism center, involving stakeholders such as local government, ecotourism managers and the media. Drone mapping reveals a variety of attractions at Mangrove Beach, but challenges such as marketing, infrastructure problems and limited shrimp cultivation skills hinder community empowerment. This program, led by the Muara Baimbai Mangrove Conservation Group, aims to increase capabilities, improve economic prosperity and environmental awareness. Identified weaknesses indicate low awareness and support. Opportunities arise from tourist interests, but threats arise from waste problems and conflicts of interest. The strategy includes mangrove management, conservation, online promotion and education, aiming to achieve a balance between conservation and economic activities, while recognizing existing challenges and the need for sustainable efforts